AVALIAÇÃO DA PROPORÇÃO DENTAL DE BOLTON EM INDIVÍDUOS COM OCLUSÃO NORMAL NATURAL E MALOCLUSÕES DE CLASSE I E CLASSE II DIVISÃO 1 DE ANGLE. - Ricci, Ivan Delgado (2010)
Introduction: The Bolton analysis, analysis that quantifies the tooth size is an important reference for professionals seeking appropriate orthodontic finishing. Objective: The objective of this study is to verify that there is discrepancy between the subjects with normal occlusion and malocclusion Class I and Class II division 1 belonging to the selected sample, compared to the values reported by Bolton and also check difference related to sexual dimorphism. Methods: 3 groups of 35 pairs of plaster casts each, separated by the type of occlusion, pertaining to the program of graduate orthodontics at the Methodist University of Sao Paulo were measured with a digital caliper at its greatest distance mesiodistal since 1st right molar to 1st molar left, the upper and lower arches, with permanent teeth. The values were tabulated and the proportion of Bolton has been applied. Results: Respectively for groups 1, 2 and 3, the total ratio found was 90.36 (SD ± 1.70), 91.17 (SD ± 2.58) and 90.76 (SD ± 2.45) and the anterior ratio was 77.73 (SD ± 2.39), 78.01 (SD ± 2.66) and 77.30 (SD ± 2.65). Conclusion: there was no sexual dimorphism or statistically significant difference compared to the values suggested by Bolton.